ANALISIS RASIO PROFITABILITAS DALAM MENGUKUR KINERJA KEUANGAN PERUSAHAAN PT. INDOFOOD SUKSES MAKMUR TBK - Laras Karim; Ilyas Lamuda; Zubaidah Rahman (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The purpose of this research is to analyze the Profitability Ratios in measuring the Financial Performance of PT. Indofood Sukses Makmur Tbk. The method used is quantitative analysis in the form of Financial Statements. The technique employed is descriptive analysis using financial ratios. The results of this research indicate that, based on the average profitability ratios from 2019-2023, the company is capable of measuring profit growth with the profitability ratio of PT. Indofood Sukses Makmur Tbk, in terms of Return on Assets (ROA), whereas Return on Equity (ROE) is still considered very low or has not yet met the industry ratio standards. The average ROA ratio is 7.84%, while the industry standard value is less than 20%, and the average ROE ratio is 14.21%, but it has not met the industry standard value of less than 25%. However, the Gross Profit Margin (GPM) exceeds the profitability industry ratio standards, as the GPM has an average ratio of 34.58%, with the industry standard ratio value being more than 30%. This indicates that the company has not yet been able to manage its finances effectively in terms of ROA and ROE, but it has managed its finances effectively in terms of GPM, meeting the operational standards.